2022
DOI: 10.1186/s12939-022-01646-z
|View full text |Cite
|
Sign up to set email alerts
|

The political economy of health financing reforms in Zimbabwe: a scoping review

Abstract: Background Implementation of health financing reforms for Universal Health Coverage (UHC) is inherently political. Despite the political determinants of UHC, health financing reform in Zimbabwe is often portrayed as a technical exercise with a familiar path of a thorough diagnosis of technical gaps followed by detailed prescriptions of reform priorities. In this study, we sought to understand the interaction between political and economic aspects of health financing reforms since the country go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 81 publications
(101 reference statements)
0
16
0
Order By: Relevance
“…The other reform driver relates to the extent to which the private sector perceives the costs and benefits arising from reforms. Private sector interests, particularly market protectionism dampened SHI and NHI oriented reforms in Ghana,43 Uganda,41 Zimbabwe24 and South Africa 39…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The other reform driver relates to the extent to which the private sector perceives the costs and benefits arising from reforms. Private sector interests, particularly market protectionism dampened SHI and NHI oriented reforms in Ghana,43 Uganda,41 Zimbabwe24 and South Africa 39…”
Section: Methodsmentioning
confidence: 99%
“…We found that political ideologies significantly influenced health reforms, particularly those with widespread redistributive effects. In the 1980s, a socialist political orientation facilitated the adoption of a well-elaborated PHC strategy in Zimbabwe that was influenced by the desire to dismantle the colonial legacy of racially driven health inequities24; a similar path taken by South Africa during the postpartheid era 40. In Ethiopia, the decision to embark on widesperead PHC reforms was rooted in the ruling coalition’s developmental state strategy with a rural bias 31.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations